Induced interpretation bias affects free recall and episodic memory bias in social anxiety. - Hye Ryeong Park; Jong-Sun Lee (PLoS ONE, 2023)
The combined effect of each cognitive bias, interpretation, attention, and memory bias, is known to play a causal role in the etiology and maintenance of social anxiety. However, little is known about how each type of bias (i.e., interpretation, memory bias) acts during social anxiety. The present study aimed to investigate whether experimentally induced interpretation bias using the cognitive bias modification (CBM) paradigm would influence free recall and episodic memory biases in a Korean sample. A total of 61 participants were randomly assigned to either a positive (n = 30) or negative (n = 31) CBM group. The study used CBM scenarios that were auditory-specific and focused on social anxiety symptoms. The results showed that interpretation biases could be induced, and they resulted in training congruent state mood and memory biases on both free-recall memory and autobiographical memory, which partly confirmed the combined cognitive biases hypothesis proposed by Hirsch, Clark (1).